Análisis de metales pesados en el cacao - Solorzano Enriquez, Kevin Fernando (Machala : Universidad Técnica de Machala, 2021)
Cocoa is an exportable item of great relevance in the Ecuadorian economy. The demand and quality of the product has led it to the international market, especially to European countries. One of the parameters that measures the quality of cocoa and its derivatives is the determination of heavy metals. The presence of heavy metals in cocoa can be an indication that soils or irrigation water could be contaminated by the action of industries and, in particular, mining; Therefore, it is necessary to determine these elements before their commercialization. Therefore, the current research aimed to identify the official methods and techniques for the quantification of heavy metals present in cocoa, through the review of national and international regulations. Given the risks that the ingestion of heavy metals represents for the environment and human health, Ecuador, through the NTE INEN - CODEX STAN 228 standard and through the methods established by AOAC 999.10 and AOAC 999.11, defines the limits allowable for Cd, As, Cu and Pb in all foods, except fats. For cocoa beans, the provisions of the EUROPEAN UNION and the Codex Alimentarius are taken as a reference, these two regulations being the most demanding at the international level. While most Latin American countries adopt their own regulations to ensure product quality and safety, all are based on international standards for the import and export of the product.
El cacao es un renglón exportable de gran relevancia en la economía ecuatoriana. La demanda y calidad del producto lo ha llevado al mercado internacional, sobre todo hacia países europeos. Uno de los parámetros que mide la calidad del cacao y sus derivados es la determinación de metales pesados. La presencia de metales pesados en el cacao, puede ser indicativo de que los suelos o el agua de riego pudieran estar contaminados por la acción de industrias y en particular la minera; por lo que resulta necesaria la determinación de estos elementos, previo a su comercialización. Por lo antes expuesto la investigación actual tuvo como objetivo identificar los métodos y técnicas oficiales para la cuantificación de metales pesados presentes en el cacao, mediante la revisión de normativas nacionales e internacionales. Dado los riesgos que representa para el medio ambiente y para la salud humana la ingestión de metales pesados, Ecuador, a través de la norma NTE INEN – CODEX STAN 228 y mediante los métodos establecidos por la AOAC 999.10 y AOAC 999.11, define los límites permisibles para Cd, As, Cu y Pb en todos los alimentos, excepto grasas. Para el grano de cacao, se toma como referencia lo establecido por la UNIÓN EUROPEA y el Codex Alimentarius, siendo estas dos normativas las más exigentes a nivel internacional. Aunque la mayoría de países latinoamericanos adoptan normativas propias para garantizar la calidad e inocuidad del producto, todos se sustentan en estándares internacionales para la importación y exportación del producto.
Keywords: CACAO; METALES PESADOS; NORMATIVAS; AOAC